Large electrostrain and high energy-storage properties of (Sr1/3Nb2/3)4+-substituted (Bi0.51Na0.5)TiO3-0.07BaTiO3 lead-free ceramics. Issue 16 (15th August 2022) - Yang, Yule; Jing, Ruiyi; Wang, Juanjuan; Lu, Xu; Du, Hongliang; Jin, Li
Abstract: In this study, we developed a novel (Sr1/3 Nb2/3 ) 4+ complex ion dopant to tailor the electrostrain and energy-storage properties of (Bi0.5 Na0.5 )TiO3 (BNT)-based ferroelectric ceramics. The chemical formula of the investigated system is [0.93(Bi0.51 Na0.5 )0.07Ba)]Ti1- x (Sr1/3 Nb2/3 ) x O3, where x  = 0.0025, 0.005, 0.0075, and 0.01. The crystal structures, microstructures, and dielectric/ferroelectric/electrostrictive/energy-storage properties of the ceramics synthesized by a solid-state reaction method were thoroughly investigated. For the x  = 0.01 composition, an ultrahigh electrostrain of 0.59 % was achieved under an electric field of 130 kV/cm. The strain response of this composition increased progressively with increasing temperature from 30 to 150 °C while maintaining good symmetry. Interestingly, the electrostrictive coefficient Q 33 was shown to be strongly temperature-sensitive. The Q 33 value was 0.018 m 4 /C 2 at 30 °C and increased dramatically as the temperature increased, reaching a maximum value of 0.0378 m 4 /C 2 at 150 °C. Furthermore, under a relatively modest electric field of 100 kV/cm, a high recoverable energy-storage density of 1.36 J/cm 3 was obtained for the x  = 0.0075 composition. These findings demonstrate that the addition of (Sr1/3 Nb2/3 ) 4+ complex ions can effectively tailor the electrostrain and energy storage properties of BNT-based ceramics. Moreover, the doping ion design principle can be applied to other BNT-based ferroelectrics, with potential for dramatic improvements in electrostrain and energy storage properties.